Sacubitril-Valsartan Lowers Blood Pressure in Patients on Dialysis: A Randomized Controlled Multicenter Study - Li Lin; Weijing Bian; Qun Luo; Liang Wang; Na Liu; Min Yang; Jun Cen; Kedan Cai; Jia Hua; Hongwei Gu; Hualin Qi; Zhihong Wang; et al. (Kidney Diseases)
Introduction: Individuals with end-stage kidney disease frequently grapple with uncontrolled hypertension, which elevates their risk for cardiovascular complications. Methods: This randomized, controlled, multicenter study, conducted across 10 hospitals, aimed to compare the effectiveness and safety of sacubitril-valsartan versus irbesartan in managing hypertension among dialysis patients. The primary efficacy variable of the present study was the reduction in office blood pressure (BP) after 12 months of treatment. Participants were randomly allocated to receive either sacubitril-valsartan (angiotensin receptor-neprilysin inhibitor [ARNI]) or irbesartan (angiotensin receptor blocker [ARB]) treatment over a 12-month period. We gauged treatment efficacy through office and 24-h ambulatory BP readings, as well as serum concentrations of N-terminal pro-brain natriuretic peptide (NT-proBNP). Safety outcomes were also evaluated. Results: Baseline office BP averaged 150/82 mm Hg and median NT-proBNP was 6,336 pg/mL. In the intention-to-treat analysis, office systolic BP reduction was significantly greater in the ARNI than ARB group (−10.4 vs. −4.6 mm Hg, p = 0.003) after adjustment for baseline BP. In hemodialysis (HD) patients, the mean systolic/diastolic BP reduction was also greater in the ARNI than ARB group (−15.9/2.4 vs. −6.6/1.1 mm Hg, p < 0.05). While for peritoneal dialysis (PD) patients, there were no significant between-group differences (p = 0.087). Per-protocol analyses in 215 patients on office BP and 137 patients on 24-h BP produced similar results. During the study period, there was no between-group difference in the overall incidence of fatal and nonfatal events and hyperkalemia. Conclusion: In dialysis patients with hypertension, especially those undergoing HD, ARNI demonstrated superior effectiveness in reducing BP compared to ARB. The safety profiles of both treatments were comparable and acceptable.